A General Continuous Flow Method for Palladium Catalysed Carbonylation Reactions Using Single and Multiple Tube‐in‐Tube Gas‐Liquid Microreactors. Issue 29 (4th September 2014) - Gross, Ulrike; Koos, Peter; O'Brien, Matthew; Polyzos, Anastasios; Ley, Steven V.
Abstract: A series of continuous flow chemistry processes that facilitate the palladium‐catalysed carbonylation of aryl and vinyl iodides and aryl bromides with a range of alkoxy, hydroxy and amino nucleophiles is reported. Harnessing a semipermeable Teflon ® AF‐2400 Tube‐in‐Tube assembly, these reactors permit the controlled transport of carbon monoxide into solution at elevated pressure to generate homogeneous flow streams, avoiding some potential issues associated with segmented flow gas‐liquid reactors. As the volume of pressurised gas contained within the device is low, the hazards associated with this are potentially mitigated relative to comparable batch processes. We also show how the incorporation of a second in‐line gas‐flow reactor allows for the sequential introduction of two gases (carbon monoxide and a gaseous nucleophile) into the reaction stream. Abstract : A Teflon ® AF‐2400 Tube‐in‐Tube reactor facilitates the use of carbon monoxide in continuous‐flow C–C bond forming reactions providing esters, amides, carboxylic acids, lactones and lactams. Two reactors can be used in series to permit the sequential addition of two reactive gases (CO and Me2 NH) into the flow stream.